Analisis Literatur Pembelajaran Tematik dalam Penguatan Karakter Jujur pada Siswa Sekolah Dasar - Agus Dwi Prasojo; Desya Rianti; Dewi Lintang Asih; Shifa Anggie Aprilia; Yessi Febrianti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to investigate the importance of character education, particularly honesty, and to consider the role of thematic learning in instilling honesty among elementary school students. The method used in this study is a qualitative approach through a literature review, 1 which includes analysis of various sources such as scientific articles, books, and previous research related to the research topic. The results of the study indicate that character education plays a very important role in developing students' character from an early age, especially in instilling ethical values such as honesty, responsibility, and discipline. It is important to instill honesty from an early age because it is the foundation for forming individuals who are reliable and able to distinguish right from wrong. Furthermore, thematic learning has proven effective in instilling honesty because it incorporates character values in learning activities that are relevant and related to everyday life. The role of teachers as role models, guides, and facilitators greatly influences the success of the character instillation process. Therefore, thematic learning can be an effective method to strengthen honesty among elementary school students through valuable learning habits and experiences.